Industrial solid waste management through sustainable green technology: Case study insights from steel and mining industry in Keonjhar, India. (2020) - Krishna, R.S.; Mishra, J.; Meher, S.; Das, Shaswat K.; Mustakim, S.M.; Singh, Saurabh K.
Abstract: The generation of industrial solid waste is increasing at an alarming rate worldwide and landfilling is no longer a feasible method for managing various industrial solid wastes. However, recent developments in environmental policies have led to many sustainable approaches towards integrated solid waste management. Industrial waste refers to the waste produced with the aid of industrial activity comprising of materials deemed useless in the production process of factories, mills, industries, and mining activities. This paper primarily focuses on waste management strategies adopted by industries: Iron & steel, mining respectively for cleaner production and sustainable development through effective utilization of solid waste in the construction industry especially in geopolymer concrete. The 21st-century demand's low carbon cement-free concrete for smart infrastructures. Geopolymer concrete, a third-generation construction material serves in effectively utilizing various industrial solid wastes generated by steel and mining industries. Short case studies have been carried out to discuss the response from the steel industry and mines towards sustainable development and waste management following the usage of GGBFS for production of geopolymer concrete thus encouraging further debate on progressive waste management strategies for a greener future.